Teleavaliação da atividade e participação após acidente vascular cerebral crônico: validação e reprodutibilidade da SATIS-Stroke - Oliveira, Léia Cordeiro de (2022)
BACKGROUND: The SATISPART-Stroke (SATIS-Stroke) is the most complete scale to assess satisfaction with activity and participation after stroke. However, its use was tested only through face-to-face interviews. OBJECTIVE: To verify the validity, reproducibility and feasibility of applying the SATIS-stroke by digital means. METHODS: Methodological study, with chronic stroke survivors, designed to validate two teleassessment modalities: self-completion of a digital form versus video call. In stage I, there was a face-to-face interview and two self-assessments, in which the participant completed the electronic form with the SATIS questions. Stage II took place 6-8 months after stage I, in which the SATIS-Stroke was replicated in person and via video call. The application order was randomized. RESULTS: A total of 95 participants were recruited, of which only 50 responded to the digital form (52.6% adherence). There were higher mean scores in the self-assessments by completing the digital form compared to the face-to-face assessment (mean difference (DM)= -0.36±0.93; p=0.009), however, with no difference between the scores of the self-assessments by completing the form. digital form. Excellent reliability was obtained in the test-retest of the self-assessment by completing the digital form (ICC2.1=0.77; 95%CI=0.60-0.87). In stage II, 50 individuals with stroke participated, with adequate reliability being observed when comparing face-to-face application vs. video call CCI2.1= 0.55; 95%CI: 0.21-0.74), with moderate correlation between the evaluation methods (r=0.43; p=0.02). Dispersion between assessments was within the limits of agreement. CONCLUSION: There was adequate validity and reliability in the assessment by digital means, with better adherence to assessment by video call.